Electrochemical Detection of Sulfite by Electroreduction Using a Carbon Paste Electrode Binder with N-Octylpyridinium Hexafluorophosphate Ionic Liquid - Aguirre-Quintana, M; Aguirre-Quintana, M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Sulfite is a widely used additive in food and beverages, and its maximum content is limited by food regulations. For this reason, determining the sulfite concentration using fast, low-cost techniques is a current challenge. This work describes the behavior of a sensor based on an electrode formed by carbon nanotubes an ionic liquid as binder, which by electrochemical reduction, allows detecting sulfite with a detection limit of 1.6 ± 0.05 mmol L−1 and presents adequate sensitivity. The advantage of detecting sulfite by reduction and not by oxidation is that the presence of antioxidants such as ascorbic acid does not affect the measurement. The electrode shown here is low-cost and easy to manufacture, robust, and stable. © 2022 by the authors.
Keywords: sulfite reduction; carbon paste electrode; ionic liquids (IL); multi-walled carbon nanotube (MWCNT)